2009
DOI: 10.1021/jf900217s
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Authentication of Olive Oil Adulteration by Raman Spectrometry

Abstract: The authentication of olive oil and its adulteration with lower priced oils are still serious problems in the olive oil industry. In this study, a method based on the intensity ratio of the Raman spectroscopy vibration bands, especially on the intensity ratio of the cis ( ==C-H) and cis (C=C) bonds normalized by the band at 1441 cm(-1) (CH(2)), was established to authenticate genuine/fake olive oil. These intensity ratios of the vibration bands given in the form of a two-dimensional chart allow first the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 31 publications
0
75
0
1
Order By: Relevance
“…European countries, such as Germany, France, Italy, Austria, Switzerland, Belgium, Spain, Portugal, Hungary, and Finland, employ PC for the determination of deteriorated oil below 25 or 27 3 , while one group 4, 5 claims that triacylglycerol oligomer content better describes the deterioration of oil and fat than PC does. In addition, methods for the determination of oil and fat deterioration such as gel-permeation liquid chromatography 6 , Fourier transform infrared spectroscopy 7 , laser desorption ionization time-of fl ight mass spectrometry 8 , Raman spectrometry 9 , fluorescence spectroscopy 10, 11 and matrix-assisted laser desorption/ionization time-of-fl ight mass spectrometry 12 are also proposed.…”
Section: Introductionmentioning
confidence: 99%
“…European countries, such as Germany, France, Italy, Austria, Switzerland, Belgium, Spain, Portugal, Hungary, and Finland, employ PC for the determination of deteriorated oil below 25 or 27 3 , while one group 4, 5 claims that triacylglycerol oligomer content better describes the deterioration of oil and fat than PC does. In addition, methods for the determination of oil and fat deterioration such as gel-permeation liquid chromatography 6 , Fourier transform infrared spectroscopy 7 , laser desorption ionization time-of fl ight mass spectrometry 8 , Raman spectrometry 9 , fluorescence spectroscopy 10, 11 and matrix-assisted laser desorption/ionization time-of-fl ight mass spectrometry 12 are also proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[15] However, two recent studies on the detection of the adulteration of VOOs have demonstrated the potential capabilities of CRS with 514.5 nm laser excitation [16] and of a portable Raman spectrometer equipped with a diode laser (785 nm). [17] Thus, FTRS has been used to determine the free fatty acids in olive fruits and olive oils, [18,19] total unsaturation in vegetable oils [20] and the water and oil contents in olive fruits and pomace [21,22] as well as to monitor the oxidation of edible oils. [23,24] However, the main applications are the authentication of the VOO and the detection of its adulteration by various edible oils: coconut, corn, garlic, grape seed, hazelnut, mustard, palm, peanut, rapeseed, safflower, sesame, sunflower, soybean, sweet almond and walnut.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, in the last decade vibrational spectroscopies have been presented as an alternative, since the analysis is fast and usually the sample preparation is very simple. [25][26][27][28][29] Raman spectroscopy is an outstanding technique in the characterization of materials because allows obtaining finger print spectra with narrow and well resolved bands and water does not generate significant interference in the signal. This technique has been used in certification, authentication, search for adulteration of products, fatty acids determinations and in the analysis of the oxidation of oils.…”
Section: Introductionmentioning
confidence: 99%